2022
DOI: 10.1111/jpc.15897
|View full text |Cite
|
Sign up to set email alerts
|

Bone kaposiform hemangioendothelioma: A rare entity dramatically improved by sirolimus

Abstract: Kaposiform hemangioendothelioma (KHE) is a rare vascular neoplasm occurring mostly in infancy or at birth. 1 In most cases, the lesion develops in soft tissues, consisting of an ill-defined cutaneous, red to purple indurated painful tumour. It may be complicated by Kasabach-Merritt phenomenon (KMP), characterised by severe thrombocytopenia and coagulation activation and rapid enlargement of the lesion. 1,2 Contiguous partial bone involvement is frequent; however, cases of deep locations and even bone location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Although 62.8% of KHE patients were reported to have musculoskeletal diseases, most of the KHE lesions were deep soft tissue that invaded bones. Lesions primarily originating from bone and limited inside bone are very rare (6). Among a series of 31 KHE patients, Kuo et al reported that there were six primary bone KHE cases involving the unilateral limb bones, spine, sacrum, scapula, and sternum (3).…”
Section: Discussionmentioning
confidence: 99%
“…Although 62.8% of KHE patients were reported to have musculoskeletal diseases, most of the KHE lesions were deep soft tissue that invaded bones. Lesions primarily originating from bone and limited inside bone are very rare (6). Among a series of 31 KHE patients, Kuo et al reported that there were six primary bone KHE cases involving the unilateral limb bones, spine, sacrum, scapula, and sternum (3).…”
Section: Discussionmentioning
confidence: 99%